In Vivo study of an intracanal dressing of calcium hydroxide/chlorhexidine in necrotic primary teeth - Gondim, Juliana Oliveira; Moreira Neto, José Jeová Siebra; Gomes, Débora Aline Silva; Azevedo, Elcilaine Rizzato; Jeremias, Fabiano; Giro, Elisa Maria Aparecida [UNESP] (UNICAMP, Faculdade de Odontologia de Piracicaba, 2014)
AIM:To evaluate the clinical and radiographic success of endodontic treatment in human primary teeth with necrotic pulp with and without radiographically visible furcal/periapical lesion treated with a calcium hydroxide (CH) and chlorhexidine (CHX) intracanal dressing. The tested hypothesis was that there is no difference in the clinical and radiographic success in primary teeth medicated with CH pastes prepared with polyethylene glycol (PEG) or CHX.METHODS:Thirty-two teeth with necrotic pulp were used in this randomized clinical study: 12 without and 20 with lesion. Canals were prepared and medicated with CH pastes with polyethylene glycol (CH/PEG) (n=16) or 2% CHX gel (CH/CHX) (n=16). Definitive filling was done after 30 days. The teeth were clinically and radiographically examined during 12 months to determine the success of the endodontic therapy. Data from clinical and radiographic examination of the initial condition and 12 months after treatment were compared using the Z test (α = 0.05).RESULTS:There was no significant difference (p>0.05) in the success rate of teeth with and without lesion medicated with CH/PEG or CH/CHX. No significant difference (p>0.05) was found between the pastes regardless of the presence of lesion.CONCLUSIONS:Combination of CHX and CH was not more effective than the CH/PEG paste, as similar clinical and radiographic success rate was observed in teeth medicated with either type of intracanal dressing.
Keywords: chlorhexidine; primary teeth; calcium hydroxide